Study on the treatment of simulated coking wastewater by O3 and O3/Fenton processes in a rotating packed bed. Issue 113 (2nd November 2015) - Wei, Qing; Qiao, Shufeng; Sun, Baochang; Zou, Haikui; Chen, Jianfeng; Shao, Lei
Abstract : A rotating packed bed was used to intensify the O3 and O3 /Fenton processes for coking wastewater treatment. Abstract : In this study, simulated coking wastewater was treated by the O3 /Fenton process in a rotating packed bed (RPB) and the results were compared with those by the O3 process. Contrast experiments indicated that the degradation rates of phenol, aniline, quinoline and NH3 –N in the wastewater reached 100%, 100%, 95.68% and 100% respectively under the optimum operating conditions in the O3 /Fenton process and were much higher than those in the O3 process. The BOD5 /COD value of the simulated coking wastewater treated in the O3 /Fenton process reached 0.46 and was 135% higher than that in the O3 process. The degradation pathways of phenol, aniline, quinoline and NH3 –N in the simulated coking wastewater were also discussed. The results indicated that a combination of the advanced oxidation processes and the RPB can enhance the treatment efficiency of coking wastewater.